Omega-3 Fatty Acids as Druggable Therapeutics for Neurodegenerative Disorders - Chitre, Neha M.; Moniri, Nader H.; Murnane, Kevin S. (CNS & Neurological Disorders - Drug Targets, 2019)
Neurodegenerative disorders are commonly associated with a complex pattern of pathophysiological hallmarks, including increased oxidative stress and neuroinflammation, which makes their treatment challenging. Omega-3 Fatty Acids (O3FA) are natural products with reported neuroprotective, anti-inflammatory, and antioxidant effects. These effects have been attributed to their incorporation into neuronal membranes or through the activation of intracellular or recently discovered cell-surface receptors (i.e., Free-Fatty Acid Receptors; FFAR). Molecular docking studies have investigated the roles of O3FA as agonists of FFAR and have led to the development of receptor-specific targeted agonists for therapeutic purposes. Moreover, novel formulation strategies for targeted delivery of O3FA to the brain have supported their development as therapeutics for neurodegenerative disorders. Despite the compelling evidence of the beneficial effects of O3FA for several neuroprotective functions, they are currently only available as unregulated dietary supplements, with only a single FDA-approved prescription product, indicated for triglyceride reduction. This review highlights the relative safety and efficacy of O3FA, their drug-like properties, and their capacity to be formulated in clinically viable drug delivery systems. Interestingly, the presence of cardiac conditions such as hypertriglyceridemia is associated with brain pathophysiological hallmarks of neurodegeneration, such as neuroinflammation, thereby further suggesting potential therapeutic roles of O3FA for neurodegenerative disorders. Taken together, this review article summarizes and integrates the compelling evidence regarding the feasibility of developing O3FA and their synthetic derivatives as potential drugs for neurodegenerative disorders.
Keywords: free fatty acid receptor